First confirmed records of the endangered Andean pitviper Bothrops lojanus Parker, 1930 (Viperidae: Crotalinae) from Peru - Carrasco P.A. (2016)
The enigmatic pitviper Bothrops lojanus, is an endangered snake known only in southwestern Ecuador. The present study confirms the presence of the species in northwestern Peru, extending its known distribution 307 km southward of the type locality of Loja.